Pentingnya Penguasaan Fungsi- Fungsi Bahasa Inggris dalam Berbicara - Ni Wayan Kasni (Linguistic Community Services Journal, 2021)
The Akasia study group is an English learning group for elementary and junior high school students located near the Warmadewa University campus. This community service is carried out in Akasia study groups in the form of English language teaching activities. Therefore, the purpose of this community service activity is to improve the English speaking’s skills of students in the Akasia study group. The method applied to this activity is the Communicative Language Taeching in Secondary Level method. In addition, this activity is carried out through the Zoom application. In these service activities, the students of the Akasia study group were enthusiastic and active in participating in learning or training. Students in the Akasia study group were given several English functions that were often used, namely greeting, asking name, and asking date, time, day year.